Antibacterial activity of silver nanoparticles obtained by pulsed laser ablation in pure water and in chloride solution - Perito, Brunella; Giorgetti, Emilia; Marsili, Paolo; Muniz-Miranda, Maurizio (Beilstein Journal of Nanotechnology, 2016)
Silver nanoparticles (AgNPs) have increasingly gained importance as antibacterial agents with applications in several fields due to their strong, broad-range antimicrobial properties. AgNP synthesis by pulsed laser ablation in liquid (PLAL) permits the preparation of stable Ag colloids in pure solvents without capping or stabilizing agents, producing AgNPs more suitable for biomedical applications than those prepared with common, wet chemical preparation techniques. To date, only a few investigations into the antimicrobial effect of AgNPs produced by PLAL have been performed. These have mainly been performed by ablation in water with nanosecond pulse widths. We previously observed a strong surface-enhanced Raman scattering (SERS) signal from such AgNPs by “activating” the NP surface by the addition of a small quantity of LiCl to the colloid. Such surface effects could also influence the antimicrobial activity of the NPs. Their activity, on the other hand, could also be affected by other parameters linked to the ablation conditions, such as the pulse width. The antibacterial activity of AgNPs was evaluated for NPs obtained either by nanosecond (ns) or picosecond (ps) PLAL using a 1064 nm ablation wavelength, in pure water or in LiCl aqueous solution, with Escherichia coli and Bacillus subtilis as references for Gram-negative and Gram-positive bacteria, respectively. In all cases, AgNPs with an average diameter less than 10 nm were obtained, which has been shown in previous works to be the most effective size for bactericidal activity. The measured zeta-potential values were very negative, indicating excellent long-term colloidal stability. Antibacterial activity was observed against both microorganisms for the four AgNP formulations, but the ps-ablated nanoparticles were shown to more effectively inhibit the growth of both microorganisms. Moreover, LiCl modified AgNPs were the most effective, showing minimum inhibitory concentration (MIC) values in a restricted range of 1.0–3.7 µg/mL. An explanation is proposed for this result based on the increased surface reactivity of the metal surface due to the presence of positively charged active sites.
Keywords: antibacterial activity; colloid; laser ablation; nanoparticles; silver